PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PENGADILAN AGAMA BEKASI KELAS 1A - Berliana Febrianti; Ni Nyoman Sawitri, Dovina Navanti, Hapzi Ali, Muhammad Asif Khan (Adisam Publisher, 2024)
This research aims to examine the influence of leadership style and organizational culture on employee performance through work motivation. This research uses a quantitative method by distributing questionnaires as a data collection tool. The number of samples used in this research was 60 respondents who were employees at the Bekasi Class 1A Religious Court. This research hypothesis testing was carried out using the outer model and inner model tests in SmartPLS with the help of the SmartPLS 4.1 program. The results of the research that has been carried out show variables that influence each other or do not influence each other, as in this brief explanation: 1). Leadership Style has a positive and significant effect on Work Motivation, 2). Organizational culture has a positive and significant effect on work motivation, 3). Leadership style has a positive but not significant effect on employee performance, 4). Organizational culture has a positive and significant effect on employee performance, 5). Work Motivation has a positive and significant effect on Performance, 6). Work Motivation has been proven to mediate Leadership Style on Performance, 7). Work Motivation is proven to mediate Organizational Culture on Employee Performance.